27. Dnevi varstvoslovja, Bohinjska Bistrica, 4. in 5. junij 2026: Zbornik povzetkov - Marina Bajić; Sotlar, Andrej; Areh, Igor; Flander, Benjamin; Modic, Maja; Pavšič Mrevlje, Tinkara (2026)
27th Days of Criminal Justice and Security, Bohinjska Bistrica, 4th & 5th of June 2026, Book of Abstracts. Contributions of the 27th Conference Days of Criminal Justice and Security represent professional and scientific consideration of paths and resources for provision of security in contemporary society. The proceeding includes abstracts of three round tables and fifty-two contributions, dealing with a broad range of topics from the field of policing, criminology, criminalistics, information security, justice, penology, military activities, general criminal justice and security, and other topics dictated by security challenges of contemporary society.
Keywords: criminal justice and security; security; policing; criminology; criminalistics; information security; penology